2019
DOI: 10.1016/j.molliq.2019.111451
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between the physical properties and biodegradability and bacteria toxicity of fatty acid-based ionic liquids

Abstract: This work is focused on the correlation between several physical properties (kinematic viscosity, viscosity index, refractive index, density and water solubility) and biodegradability and bacteria toxicity of a family of ionic liquids synthesized from fatty acids as anion precursor (FAILs): methyltrioctylammonium hexanoate [N 8881 ][C 6:0 ], methyltrioctylammonium octanoate [N 8881 ][C 8:0 ], methyltrioctylammonium laurate [N 8881 ][C 12:0 ], methyltrioctylammonium palmitate [N 8881 ][C 16:0 ], methyltrioctyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 37 publications
(43 reference statements)
1
19
0
Order By: Relevance
“…In addition, Yu et al [63] observed that longer alkyl chain makes the salt more viscous because of an increase in van der Waals interactions. However, both properties decrease in this research with the increase of the alkyl chain length of the anion, similarly to other FAILs employed in previous research works [64][65][66][67]. The differences in viscosity behavior could be explained in a similar way that what happen with surface tension [46].…”
Section: Density Viscosity and Thermal Propertiessupporting
confidence: 80%
See 1 more Smart Citation
“…In addition, Yu et al [63] observed that longer alkyl chain makes the salt more viscous because of an increase in van der Waals interactions. However, both properties decrease in this research with the increase of the alkyl chain length of the anion, similarly to other FAILs employed in previous research works [64][65][66][67]. The differences in viscosity behavior could be explained in a similar way that what happen with surface tension [46].…”
Section: Density Viscosity and Thermal Propertiessupporting
confidence: 80%
“…, the[N 6,6,6,6 ][C 16:0 ] IL has the highest viscosity index, showing that an increase in the alkyl chain length improves the lubrication potential of the FAIL[64,67].…”
mentioning
confidence: 99%
“…Furthermore, the cation and/or anion amphiphilic nature can be finely balanced to trigger the self-assembling behavior of ILs [ 40 , 41 , 42 , 43 , 44 ]. In this framework, fatty acids raised remarkable interest as building blocks for ILs containing natural hydrophobic tails [ 45 , 46 , 47 , 48 , 49 , 50 ] and such materials were investigated in pharmaceutical applications [ 42 , 51 , 52 , 53 , 54 ]. An intriguing subclass of ILs is that of the so-called protic ionic liquids (PILs), which are easily prepared by reacting a Brønsted acid and a Brønsted base [ 55 , 56 ].…”
Section: Introductionmentioning
confidence: 99%
“…To understand the correlation between the molecular structure and biodegradability and toxicity of ILs is essential to design green IL lubricants. Nowadays, many experimental studies [21,33] have been conducted to evaluate the environmental impact of ILs. In addition, computational approaches [34][35][36] are also employed to assess their toxicity.…”
Section: Biodegradability and Toxicitymentioning
confidence: 99%